PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN IPAS KELAS IV SDN 18 MUARA TEBO KABUPATEN TEBO - Amril; Agus Saputra; Uli Ulya (STKIP Subang, 2023)
This research is motivated by the difficulties of students in preparing learning media, in the learning process, especially historical material, landscapes and community culture, media is needed in conveying learning. For this reason, it is necessary to have an innovation in the learning process for students to improve learning outcomes. This type of research is development research using the ADDIE model. The ADDIE model has five stages, namely: Analyze, Design, Development, Implementation, Evaluation. Analyze stage, at this stage needs analysis, material analysis, student analysis are carried out. Design stage, the design stage is carried out by designing instruments, products, questionnaires and test questions. Development stage, which carried out a validation test. Implementation phase, at this stage practicality and effectiveness are carried out. Evaluation stage, at this stage which is carried out at each stage starting from Analyze, Design, Development, Implementation, Evaluation. As for the results of the development of augmented reality-based learning media obtained from 3 validators, augmented reality-based learning media obtained a percentage with an average of 89.3% with a very valid category. The practicality results assessed from the teacher's response questionnaire obtained a percentage with an average of 90.8% in the very practical category and the student response questionnaire obtained a percentage with an average of 88.17% with a very practical category. The results of the practicality of 23 students who took part in learning using the media developed in material 1 stated that 78.26% completed material 2 stated 82.60% complete and material 3 obtained 91.3% complete categorized as very practical in terms of use.